The Effects of Marketing Practices – Business Strategy Alignment on Performance - Matos, Celso Augusto de (2018)
Purpose: This study aimed to investigate the extent to which a greater alignment between marketing strategy and business strategy produces higher firm performance, taking into account the use of marketing and financial metrics. Method: A survey was carried out with 238 companies from the southern region of Brazil. Data are analyzed using factor analysis and multiple regression. Results: Results demonstrate that companies with greater alignment between marketing practices and business strategy presented higher performance, i.e. market share, sales increase and profitability. More specifically, performance was greater in the group of prospectors using aggressive marketing, corresponding to 29% of the sample. Findings also showed that the marketing practice most strongly associated with firm performance is product/service quality. Theoretical Contributions: The study contributes to the strategic marketing literature by (i) analyzing which marketing practices are more strongly associated with greater firm performance and (ii) evaluating which business strategy typology conduct to a greater performance. Moreover, the metrics of return on sales and return on advertising were the two more strongly associated with performance. Originality/relevance: The current study advances the strategic marketing literature by demonstrating that firm performance is superior in the group of firms that combines aggressive marketing as a marketing strategy with prospectors as a business strategy. In addition, we take into account the use of different marketing and financial metrics.